Macular Hole of the Left Eye in a 41-year-old Patient with Retinitis pigmentosa. A Case Report - Bożena Kmak; Tomasz Siewierski; Anna Szot; Sebastian Sirek (Okulistyka)
Retinitis pigmentosa is characterized by degeneration of the photoreceptors or retinal pigment epithelium and causes progressive vision loss. The disease can lead to night blindness, reduced field of vision and finally to complete loss of vision. The report describes a case of a patient diagnosed with retinitis pigmentosa who was admitted to hospital for further diagnosis and treatment. For several months, the patient reported a gradual decrease in visual acuity, especially in the left eye and visual impairments in poor lighting. Retinitis pigmentosa is a genetic disorder, therefore genetic counseling and screening of family members for retinitis pigmentosa is important. The specific pharmacological treatment is still unknown. In severe cases posterior vitrectomy is performed as a basic method of curing macular holes.